2009
DOI: 10.15288/jsads.2009.s16.5
|View full text |Cite
|
Sign up to set email alerts
|

NIAAA's Rapid Response to College Drinking Problems Initiative: Reinforcing the Use of Evidence-Based Approaches in College Alcohol Prevention

Abstract: ABSTRACT. Objective: The National Institute on Alcohol Abuse and Alcoholism (NIAAA) created the Rapid Response to College Drinking Problems initiative so that senior college administrators facing an alcohol-related crisis could get assistance from well-established alcohol researchers and NIAAA staff. Method: Based on a competitive grant process, NIAAA selected fi ve teams of research scientists with expertise in college drinking research. NIAAA then invited college administrators to propose interventions to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 36 publications
0
40
0
1
Order By: Relevance
“…ACH YEAR, COLLEGE STUDENT DRINKING leads to deaths, injuries, physical assaults, and sexual assaults and remains cause for serious concern (DeJong et al, 2009; National Institute on Alcohol Abuse and Alcoholism [NIAAA], 2002). Frequency and typical (average) volume of alcohol consumed by college students are most commonly studied, but an important and understudied aspect of college student drinking is the pattern of drinking, which captures the timing and quantities of drinking.…”
mentioning
confidence: 99%
“…ACH YEAR, COLLEGE STUDENT DRINKING leads to deaths, injuries, physical assaults, and sexual assaults and remains cause for serious concern (DeJong et al, 2009; National Institute on Alcohol Abuse and Alcoholism [NIAAA], 2002). Frequency and typical (average) volume of alcohol consumed by college students are most commonly studied, but an important and understudied aspect of college student drinking is the pattern of drinking, which captures the timing and quantities of drinking.…”
mentioning
confidence: 99%
“…x V nadaljevanju (Tabela 2) so povzete ugotovitve 19 člankov (iz tabele izključeni pregledni članki (33)(34)(35)(36)). Pokazalo se je, da je nekaj takšnih raziskav, kjer je bilo bodisi nemogoče določiti, kakšen je rezultat (oznaka 0 v Tabeli 2) ali pa sta v zaključku tako pozitiven, kot negativen rezultat.…”
Section: Vrsta Raziskave (Vir)/type Of Research (Source) Ukrep/intervunclassified
“…Therefore, the widespread assumption that information provision on risks and dangers of drugs and harmful behaviour would allow adolescents to take 'informed choices' (Advisory Committee on Drug Misuse, 2006) boldly ignores what is known about adolescent functioning. In contrast, in a review for the National Institute on Alcohol Abuse and Alcoholism's (NIAAA) Rapid Response to College Drinking Initiative (DeJong, Larimer, Wood & Hartman, 2009) orientation sessions, awareness weeks or provision of alcohol-related facts were classified as 'evidence of ineffectiveness', while environmental approaches, all of a normative nature, were rated with 'evidence of success with general populations' .…”
Section: What Is the Problem With Information Approaches?mentioning
confidence: 99%
“…The effectiveness of environmental prevention regarding alcohol has been well established (Room, Babor & Rehm, 2005), as it has in university settings (DeJong et al, 2009). As for the spin-off effects between regulation of tobacco and use of cannabis, there is some evidence that tobacco smoking is associated with cannabis use (Vega, 2005;Wetzels, Kremers & Vitoria, 2003) and a recent French study (Mayet, Legleye, Chau & Falissard, 2010) found that tobacco smoking can mediate the initiation into cannabis use.…”
Section: Does It Work?mentioning
confidence: 99%